2005
DOI: 10.1590/s0100-879x2005000700007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of D-alpha-tocopherol on tubular nephron acidification by rats with induced diabetes mellitus

Abstract: The objective of the present study was to determine if treatment of diabetic rats with D-alpha-tocopherol could prevent the changes in glomerular and tubular function commonly observed in this disease. Sixty male Wistar rats divided into four groups were studied: control (C), control treated with D-alpha-tocopherol (C + T), diabetic (D), and diabetic treated with D-alpha-tocopherol (D + T). Treatment with D-alpha-tocopherol (40 mg/kg every other day, ip) was started three days after diabetes induction with str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
4
0
2
Order By: Relevance
“…[ 55 ] Studies in animal models have shown that antioxidant therapy has beneficial effects. [ 56,57 ] However, the results of antioxidant therapy in patients with DN are limited and partially conflicting. [ 15,17,32,58 ] Therefore, we collected data from 25 studies to evaluate the role of antioxidants in the treatment of DN.…”
Section: Discussionmentioning
confidence: 99%
“…[ 55 ] Studies in animal models have shown that antioxidant therapy has beneficial effects. [ 56,57 ] However, the results of antioxidant therapy in patients with DN are limited and partially conflicting. [ 15,17,32,58 ] Therefore, we collected data from 25 studies to evaluate the role of antioxidants in the treatment of DN.…”
Section: Discussionmentioning
confidence: 99%
“…There are reports glomerular hypertrophy being inhibited through consumption of herbal antioxidants extracts such as garlic, ginger [ 38 ], and Ginkgo biloba [ 39 ] in diabetic animals. In addition, glomerular hypertrophy has been inhibited by antioxidants such as vitamin E and α-tochopherol in diabetic rats [ 40 , 41 ]. Anthocyanins are widely distributed in human diets, suggesting that we ingest large amounts of anthocyanins from plant-based foods.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycaemia increases reactive oxygen species (ROS) production and activates the RAS, which leads to further increases in ROS production. Previous studies using experimental diabetic models suggest positive effects of anti‐oxidant treatment on diabetic complications …”
Section: Introductionmentioning
confidence: 99%